Femtosecond laser hybrid processing strategy of transparent hard and brittle materials - Tan, Jia-Wei; Wang, Gong; Zhao, Guo-Xu; Hou, Ya-Chong; Sun, De-Rong; Song, Yi-Fei; Dong, Le-Yan; Zhao, Hui; Wang, Yulei (Frontiers in Chemistry, 2022)
With high hardness, high thermal stability, chemical inertness and excellent optoelectronic properties, transparent hard and brittle materials have drawn significant attentions in frontier domains such as aerospace, photoelectric detection, and high-intensity lasers. Femtosecond laser processing technology demonstrates great potential for transparent hard and brittle materials processing due to its outstanding advantages such as non-contact, true 3D processing and programmable design. However, high-energy laser ablation usually causes severe damage to the surface of the materials, resulting in low processing accuracy, low processing efficiency and poor surface quality. Femtosecond laser hybrid processing strategies have been proven to be an effective solution to solve the above problems. This mini-review summarizes the fundamentals and research progress of femtosecond laser hybrid processing strategies of transparent hard and brittle materials in recent years. Moreover, the challenges and application prospects of these techniques are discussed.